PENGUATAN KREATIVITAS SISWA MELALUI KEGIATAN PANGGUNG KREATIVITAS DI SDN KARANGANYAR GUNUNG 02 - Windi Widyayati; Husni Wakhyudin; Noor miyono; Nur Riskiyati (STKIP Subang, 2023)
This study aims to analyze the creativity of students at school through routine habituation of the creativity stage at SDN Karanganyar Gunung 02. Education in elementary schools has an important role in developing student creativity, one way to develop student creativity is through habituation to the creativity stage. The creativity stage is a routine activity carried out to develop the creativity and talents and interests of students. There is a correlation between the habituation of the creativity stage at SDN Karanganyar Gunung 02 every Tuesday and the students creative abilities. The positive correlation is the stage of creativity as forum for developing the creativity of students through performances or performances that are carried out in turn from each clas, besides that the stage of creativity can also foster self confidence and hone studens interest and talents in creating. Teachers can develop students creativity by providing activities according to the needs and interest of students, through the creativity stage students can be taught to choose and determine what the will do to appear, the appearance of students is adjusted to their ideas and creativity and their creations are in accordance with tehe wishes of the participants educate.